2006
DOI: 10.1111/j.1750-3841.2006.00099.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Thermal Process Time on Quality of “Shrimp Kuruma” in Retortable Pouches and Aluminum Cans

Abstract: The effect of processing time on biochemical, sensory characteristics, and instrumental texture profiles of “Shrimp Kuruma” in retortable pouches and aluminum cans with equal pack weight and lethality was studied. Processing in pouches resulted in a 35% reduction in processing time compared to cans for equal lethality (F0 8.0). Thermal processing resulted in a 14% loss of water in canned samples compared to 9% in pouched products. Thermal processing resulted in an increase in the volatile compounds and a decre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
38
1
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(46 citation statements)
references
References 19 publications
6
38
1
1
Order By: Relevance
“…6.6 ± 0.1 1 6.4 ± 0.1 2 6.2 ± 0.1 3 6.1 ± 0.1 4 6.1 ± 0.1 5 6.0 ± 0.5 6 5.9± 0.1 7 5.8 ± 0.1 8 5.7 ± 0.1 Table.5 Changes in TVB-N content of eel in curry product during storage at ambient temperature The commonly observed decrease in pH might be due to degradation of proteins and liberation of free amino acids (Rajan et al, 2011). The results are in accordance with the studies conducted by Mohan et al, (2006) has reported a slight reduction in the pH of shrimp kuruma upon storage in both retort pouch and aluminium cans.In case of mackerel curry packed in retort pouch, Mallick et al, (2006) observed decrease in pH values from 5.8 to 5.43 at room temperature and 5.65 to 5.55 at 37 o C during 6 months storage of rohu in curry medium using polyester-coated tin free steel cans. Similarly Ravishankar et al, (2008) and Tribuzi et al, (2015) observed decreasing trend in pH values from 5.5 to 5.25 and 6.72 to 6.63 during 12 months storage of Goan style mackerel curry in retort pouch and 52 weeks storage of chopped mussel meat in retort pouch respectively.…”
Section: Changes In Biochemical Characteristicssupporting
confidence: 81%
See 1 more Smart Citation
“…6.6 ± 0.1 1 6.4 ± 0.1 2 6.2 ± 0.1 3 6.1 ± 0.1 4 6.1 ± 0.1 5 6.0 ± 0.5 6 5.9± 0.1 7 5.8 ± 0.1 8 5.7 ± 0.1 Table.5 Changes in TVB-N content of eel in curry product during storage at ambient temperature The commonly observed decrease in pH might be due to degradation of proteins and liberation of free amino acids (Rajan et al, 2011). The results are in accordance with the studies conducted by Mohan et al, (2006) has reported a slight reduction in the pH of shrimp kuruma upon storage in both retort pouch and aluminium cans.In case of mackerel curry packed in retort pouch, Mallick et al, (2006) observed decrease in pH values from 5.8 to 5.43 at room temperature and 5.65 to 5.55 at 37 o C during 6 months storage of rohu in curry medium using polyester-coated tin free steel cans. Similarly Ravishankar et al, (2008) and Tribuzi et al, (2015) observed decreasing trend in pH values from 5.5 to 5.25 and 6.72 to 6.63 during 12 months storage of Goan style mackerel curry in retort pouch and 52 weeks storage of chopped mussel meat in retort pouch respectively.…”
Section: Changes In Biochemical Characteristicssupporting
confidence: 81%
“…These decreasing trends of texture profiles were mainly due to the increase in the heat treatment (Majumdar et al, 2015). Sreenath et al, (2008) noted the decreasing in texture profile of shrimp curry processed for different F 0 values at 121 o C. Majumdar et al, (2015) observed the decreasing trend in texture profile of rohu curry processed at 121.1 o C. Mohan et al, (2006) reported the decreasing trend in texture profile of 'Shrimp Kuruma' in retort pouch and aluminium cans.…”
Section: Texture Profile Analysismentioning
confidence: 91%
“…The lower lightness value showed the darker color of sample. Mohan et al (2006) reported the darker color of shrimp kuruma in cans which was cooked for longer time. During 3 wks storage, the lightness of packed Dakgalbi which was stored on a refrigerator remained stable while the other packed Dakgalbi stored on room temperature was increased on 1 and 2 wk then again declined on 3 wk of storage.…”
Section: Instrumental Colormentioning
confidence: 99%
“…The advantage of retort pouch pack in comparison with other thermal processing pack is the shorter cooking time because of its high ration of surface area to volume, so that it has better taste, improved nutritional value and less moisture loss (Trevino, 2009). Retort packaging was commonly used for packaging of various kinds of seafood products, such as sardines (Ali et al, 2005), tuna (Ali et al, 2006), fowl meat (Lyon and Klose, 1981), shrimp (Mohan et al, 2006) but there is only few study on meat products, for instance vegetables with bacon (Heidelbaugh and Karel, 1970) and beef stew (Cremer and Pizzimenti, 1992).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation